Prevalence of poor sleep quality in COVID-19 patients: a systematic review and meta-analysis - Gui, Zhen; Wang, Yue-Ying; Li, Jia-Xin; Li, Xiao-Hong; Su, Zhaohui; Cheung, Teris; Lok, Ka-In; Ungvari, Gabor S.; Ng, Chee H.; Zhang, Qinge; Xiang, Yu-Tao (Frontiers in Psychiatry, 2024)
Objective The coronavirus disease (COVID-19) and the public health responses were associated with a huge health burden, which could influence sleep quality. This meta-analysis and systematic review examined the prevalence of poor sleep quality in COVID-19 patients. Methods PubMed, Web of Science, Embase, and PsycINFO were systematically searched from their respective inception to October 27, 2022. Prevalence rates of poor sleep were analyzed using a random effects model. Results Totally, 24 epidemiological and 12 comparative studies with 8,146 COVID-19 patients and 5,787 healthy controls were included. The pooled prevalence of poor sleep quality based on the included studies was 65.0% (95%CI: 59.56–70.44%, I2 = 97.6%). COVID-19 patients had a higher risk of poor sleep quality compared to healthy controls (OR = 1.73, 95% CI: 1.30–2.30, p < 0.01, I2 = 78.1%) based on the 12 comparative studies. Subgroup analysis revealed that COVID-19 patients in low-income countries (p = 0.011) and in studies using a lower Pittsburgh Sleep Quality Index score cut-off (p < 0.001) were more likely to have poor sleep quality. Meta-regression analyses revealed that being female (p = 0.044), older (p < 0.001) and married (p = 0.009) were significantly correlated with a higher risk of poor sleep quality while quality score (p = 0.014) were negatively correlated with the prevalence of poor sleep quality in COVID-19 patients. Conclusion Poor sleep quality was found to be very common in COVID-19 patients. Considering the negative effects of poor sleep quality on daily life, sleep quality should be routinely assessed and appropriately addressed in COVID-19 patients.